ANALISIS PENDAPATAN USAHA PETANI JERUK MELALUI PEMBIAYAAN KREDIT USAHA RAKYAT BNI DI DESA PETUNGSEWU KECAMATAN DAU KABUPATEN MALANG - Mustafidah, Hidayatul; Boedirochminarni, Arfida (Journal of Financial Economics & Investment, 2022)
This study aims to analyze the income of citrus farmers and the effect of land area, production costs and BNI (Kredit Usaha Rakyat) KUR capital on the income of citrus farmers in Petungsewu Village, Dau District, Malang Regency. This type of research is descriptive quantitative using primary data sources and secondary data. Data collection methods are interviews and questionnaires. The population and sample in this study amounted to 21 people with the criteria of citrus farmers using KUR BNI. The independent variables in this study are land area, production costs and capital  BNI KUR on the income of citrus farmers. The result of this research is that land area has a positive and significant effect on the income of citrus farmers. Production costs have a positive and significant effect on the income of citrus farmers. Capital (KUR BNI) has a positive and insignificant effect on the income of citrus farmers.